Conditionality in development aid policy - Andrea Schmitz (Stiftung Wissenschaft und Politik (SWP), 2006)
The disappointing results of development aid policy have discredited traditional incentive-based conditionality and have unleashed a debate on the effectiveness of development aid. There is now a consensus that sustainable reforms cannot be imposed, rather it is necessary that recipients be willing to take responsibility for formulating and implementing reform programs with the financial and technical support of the donors.The new paradigm of development partnership is accompanied by a continuing debate over re-designing conditionality. This signals an effort to translate contradictory demands and goals into consistent policy programs which are above all efficient in aiding development. This study offers orientation in this debate by identifying the options for applying conditionality: an exclusive approach, which calls for a stricter selectivity in the choice of partners, and an inclusive approach, which conceives of conditionality as knowledge transfer and a learning process. The performance of both strategies is exemplified by the conditionality of the Millennium Challenge Account and the development aid of the EU.It becomes clear that a selective strategy does not promise much success with regard to a more efficient ressource allocation and cannot be implemented consistently. In contrast, the example of EU programs demonstrates that when conditionality is framed as development partnership, it is a powerful instrument of political influence which expects the recipients to take ownership of reform programs and hence tends to delegate the responsibility for their impact and consequences to the recipents. (SWP-Research Papers / SWP)
Keywords: 320; Europäische Union